2020
DOI: 10.1021/acs.est.9b05784
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and Distribution of Naphthenic Acids in the Produced Water from Offshore Norwegian North Sea Oilfields

Abstract: Naphthenic acids (NAs) constitute one of the toxic components of the produced water (PW) from offshore oil platforms discharged into the marine environment. We employed liquid chromatography (LC) coupled to high-resolution mass spectrometry with electrospray ionization (ESI) in negative mode for the comprehensive chemical characterization and quantification of NAs in PW samples from six different Norwegian offshore oil platforms. In total, we detected 55 unique NA isomer groups, out of the 181 screened homolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 41 publications
(105 reference statements)
1
19
0
Order By: Relevance
“…Extracts of naphthenic acid from produced water were shown to have an EC50 of 23 mg/L for S. costatum and 6.4 mg/L for A. tonsa (Frost et al, 2003). Assuming that naphthenic acid concentrations in the present study are in the same range as those measured in the past (Bertheussen et al, 2021; Mediaas et al, 2003; Samanipour et al, 2020), they could have contributed to the toxicity observed in the present WET tests. Recently, a standardized method for routine chemical characterization of the total concentration of naphthenic acids (as a group) in produced water effluents was developed (Bertheussen et al, 2021) and is currently implemented in the biannual analysis of produced water effluents on the Norwegian continental shelf.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Extracts of naphthenic acid from produced water were shown to have an EC50 of 23 mg/L for S. costatum and 6.4 mg/L for A. tonsa (Frost et al, 2003). Assuming that naphthenic acid concentrations in the present study are in the same range as those measured in the past (Bertheussen et al, 2021; Mediaas et al, 2003; Samanipour et al, 2020), they could have contributed to the toxicity observed in the present WET tests. Recently, a standardized method for routine chemical characterization of the total concentration of naphthenic acids (as a group) in produced water effluents was developed (Bertheussen et al, 2021) and is currently implemented in the biannual analysis of produced water effluents on the Norwegian continental shelf.…”
Section: Discussionsupporting
confidence: 65%
“…In the past, naphthenic acids have been isolated from the effluent of installation Heidrun and were measured at concentrations of roughly 50 mg/L (Mediaas et al, 2003). Similar levels have been found in produced water more recently as well (Bertheussen et al, 2021;Samanipour et al, 2020). Toxicity to aquatic species justified considering naphthenic acids as a produced water constituent of concern (Jones et al, 2011;Thomas et al, 2009).…”
Section: Practical and Methodological Considerationsmentioning
confidence: 87%
“…Vanadium compounds; 296 Non-polar aromatic compounds; 297 thiols; [298][299][300] Sulfides; 301,302 N-, S-, and O-containing species; 129,198,205,207,212,214,221,224,236,244, Porphyrins; [348][349][350][351][352] Molecular structure of Asphaltenes; 185,216,353,354 naphthenic acids; 284,285,[355][356][357][358][359][360] petroleum sulfonates; [361][362][363][364] acidic compounds; 213,215,216,323,362,[365][366][367][368][369][370][371]…”
Section: Esi (Electrospray Ionization)mentioning
confidence: 99%
“…Another study detected 55 unique NAs isomer groups in PW samples from different Norwegian offshore oil platforms with carbon number ranging from 8 to 26 and Z values of 0 to −18. Based on NAs distribution and the concentration in the samples, the C 8 H 14 O 2 isomer group appeared to be an indicator of the presence of NAs in the samples [142].…”
Section: Carbon Number (N)mentioning
confidence: 99%